Motivations and Barriers Associated With Physician Volunteerism for an International Telemedicine Organization - Kim, Erin J.; Fox, Steven; Moretti, Meghan E.; Turner, Michelle; Girard, Timothy D.; Chan, Stephen Y. (Frontiers in Public Health, 2019)
Introduction: The Addis Clinic uses volunteer physicians to implement an international humanitarian telemedicine program. We sought to identify motivations and barriers that may contribute to physician volunteerism in international telemedicine. Methods: We surveyed active and inactive volunteers working with The Addis Clinic. Descriptive statistics were used to examine closed-ended questions, while a qualitative approach identified overarching themes for open-ended questions. The Volunteer Functions Inventory framework was also applied. Results: Among 69 active and 25 inactive volunteers, survey response rates of 74 and 72%, respectively, were attained. Volunteer cohorts exhibited comparable distributions across sex, marital status, and children. Active, as compared with inactive, participants were significantly more likely to be <40 years old (51 vs. 39%, p = 0.01), have prior experience with international/global health (67 vs. 39%, p = 0.04), and express an interest in international/global health work (82 vs. 50%, p = 0.008). Active volunteers were predominantly concerned with challenges regarding patient care: they more often reported the asynchronous nature of communication with frontline health workers as a significant barrier (37 vs. 6%, p = 0.047), and increased patient follow-up significantly drove their enthusiasm (64 vs. 35%, p = 0.05). Conversely, active volunteers were less likely to cite commitment/availability as a significant barrier for participation (33 vs. 72%, p = 0.002), less likely to be incentivized by opportunities to fulfill professional obligations (14 vs. 59%, p = 0.001), and more likely to be satisfied with the telemedicine experience (86 vs. 0%, p < 0.0001). Opportunities to receive remuneration or recognition did not increase the likelihood of volunteering for either cohort. Malpractice concerns were cited in a comparable minority across cohorts (20 vs. 17%). Conclusions: Age and global health experience/interest were significant predictors of physician volunteerism. While inactive volunteers reported time commitment as a barrier, active participants were concerned with challenges regarding patient care and motivated by increased methods to connect with patients. Financial considerations and recognition were infrequently reported as a barrier. With advances in telemedicine globally, results from this study can be used by organizations involved in international telemedicine to develop effective volunteer recruitment and retention strategies.